2010
DOI: 10.5897/jmpr09.438
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, characterization and antitumor effect of the polysaccharides from star anise (Illicium verum Hook. f.)

Abstract: Polysaccharides production from star anise was carried out. The effects of extraction temperature, time, ratio of water to raw material and number of extraction were optimized by using an orthogonal L9 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This is attributed to its demonstrated effectiveness in antimicrobial, antifungal, and antioxidant activities (Benmalek et al., 2013; Chouksey & Sharma, 2010). Star anise reportedly is utilized in treatment of various diseases, such as infantile colic and metastatic cancer (Li & Xu, 2020; Shu et al., 2010). Additionally, a promising COVID‐19 main protease inhibitor was identified from star anise (Tripathi et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to its demonstrated effectiveness in antimicrobial, antifungal, and antioxidant activities (Benmalek et al., 2013; Chouksey & Sharma, 2010). Star anise reportedly is utilized in treatment of various diseases, such as infantile colic and metastatic cancer (Li & Xu, 2020; Shu et al., 2010). Additionally, a promising COVID‐19 main protease inhibitor was identified from star anise (Tripathi et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The extracted shikimic acid is one of the main ingredients of the antiviral drug Tamiflu ® (oseltamivir) that is used to treat symptoms caused by avian influenza [98]. It has also been reported to have antimicrobial properties [99] and antioxidant properties [100], as well as significant anti-cancer potential [101]. There are studies in which star anise has been used as an insect repellent, such as for the Indian flour moth (P. interpunctella larvae) [102,103].…”
Section: Essential Oils In Plantsmentioning
confidence: 99%
“…Modern pharmacological investigations demonstrated that I. verum possessed antiviral, , antioxidant, , antitumor, , antibacterial, , insecticidal, , anti-inflammatory, , analgesic, and neuroprotective activities. Previous phytochemical studies on I.…”
Section: Introductionmentioning
confidence: 99%